Renal Denervation in Resistant Hypertension and Obstructive Sleep Apnea: Randomized Proof-of-Concept Phase II Trial. Issue 2 (August 2018) - Warchol-Celinska, Ewa; Prejbisz, Aleksander; Kadziela, Jacek; Florczak, Elzbieta; Januszewicz, Magdalena; Michalowska, Ilona; Dobrowolski, Piotr; Kabat, Marek; Sliwinski, Pawel; Klisiewicz, Anna; Topor-Madry, Roman; Narkiewicz, Krzysztof; et al.
Abstract : It has been postulated that catheter-based renal denervation (RDN) may lower blood pressure (BP) and improve severity of obstructive sleep apnea (OSA) in resistant hypertensive patients. The aim of our study (NCT01366625) was to investigate in a prospective randomized trial the effect of RDN on BP and clinical course of OSA. Sixty patients with true resistant hypertension coexisting with moderate-to-severe OSA (apnea/hypopnea index, ≥15) were randomly allocated to RDN group (30 patients) and to control group (30 patients). The primary end point was reduction in office systolic BP at 3 months. Secondary end points included reduction in diastolic office and ambulatory BP, change in apnea/hypopnea index and biochemical measurements at 3 months, and change in echocardiographic measurements at 6 months. There were no differences in clinical characteristics between the groups. At 3 months in the RDN group, both office and ambulatory BP were significantly reduced, and a significant decrease in OSA severity (apnea/hypopnea index, 39.4 versus 31.2 events per hour; P =0.015) was observed. Between-group difference in apnea/hypopnea index change was significant at 0.05. At 6 months in the RDN group, reductions in office and ambulatory BP were sustained and were accompanied by significant improvement in echocardiographic measures of global longitudinal strain. There were no differences in metabolic variables in follow-up in both groups. In a randomized controlled trial, RDN lowered both office and ambulatory BP in patients with resistant hypertension and OSA. This was accompanied by improvement of the clinical severity of OSA. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01366625. Abstract : Supplemental Digital Content is available in the text.